Effect of compatibilizer, MAPP, on physical and mechanical properties of reed stem flour- polypropylene composites - Fataneh Azad (Regional Information Center for Science and Technology (RICeST), 2009)
In order to investigate the effect of compatibilizer, (MAPP), on physical and mechanical properties of reed stem flour- polypropylene composites, 60 mesh size reed stem flour particles were compounded at 60% and 70% by weight with a polypropylene homopolymer with a melt flow index of 18 g/10min. Two compounds were prepared from which formulations with 60 mesh particle size and 60% and 70% filler loading were selected to evaluate the role of the compatibilizer. One of them was without MAPP and the other one had 3% MAPP by weight. Totally, 4 compounds were prepared. Composites were produced using a twin screw counter rotating extruder. Then, mechanical tests including static flexural test, tensile test, Izod impact test and hardness test were carried out. Physical tests including water absorption and thickness swelling were also performed. All testing was in accordance with ASTM D7031-04 specification. The results of physical tests have indicated that by the increase in reed flour content, maximum water absorption and maximum thickness swelling increased. Generally, by adding the coupling agent (MAPP), the physical and mechanical properties significantly improved.